Improving the performance of classification models with fuzzy cognitive maps - Christodoulou, Panayiotis; Christoforou, Andreas; Andreou, Andreas S. (My University, 2017)
This paper presents a novel approach to improve the accuracy of classification models used for prediction purposes by integrating a Fuzzy Cognitive Map (FCM) to produce a hybrid model. The proposed methodology first uses the FCM to discover latent correlations that exist between the data in order to form a single variable. This variable is then fed in the classification model as part of the training and testing phases to enhance its accuracy. Experimental results using datasets describing two different problems suggested noteworthy improvements in the accuracy of various classification models.
Keywords: Classification models; Fuzzy Cognitive Maps; Prediction accuracy